Dynamika wód podziemnych poziomów czwartorzędowych w międzyrzeczu Nysy Łużyckiej i Lubszy w województwie Zielonogórskim = The dynamics of the underground waters of quaternary horizons in a region situated between rivers Nysa Łużycka and Lubsza in Zielona Góra voivodship - Wróbel, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the period 1976-1986 in a region situated between rivers Nysa Łużycka and Lubszasystematic measurements of the underground water levels and their changes of thehydrochemical nature were carried out. The observations were continued, because inJanschwalde-Forst (GDR) a lignite strip mine was constructed and was necessary tostudy the influence of this mine on the water conditions in Polish People's Republicin the zone between Gubin and Zasieki. In this paper were presented only the problems of dynamics of the underground waters from the Quaternary horizons. The result of the investigations allowed for:
Keywords: wody gruntowe; Nysa Łużycka; Lubsza; badania